Compatibility Conditions and the Convolution of Functions and Generalized Functions - Andrzej Kamiński; Svetlana Mincheva-Kaminska (Journal of Function Spaces and Applications)
The paper is a review of certain existence theorems concerning the convolution of functions, distributions, and ultradistributions of Beurling type with supports satisfying suitable compatibility conditions. The fact that some conditions are essential for the existence of the convolution in the discussed spaces follows from earlier results and the proofs given at the end of this paper.